Python - Based Image Processing - K H, Mrs. Asha; B E, Manjunathswamy; A S, Mrs. Chaithra (International Journal of Scientific Research and Management (IJSRM), 2021)
The main goal of the Image Process project is to extract important information from photographs. The machine may produce a description, interpretation, and comprehension of the scene based on this extracted data. The main goal of image processing is to transform photos in the desired way. This technique allows users to obtain the text of picture processing printing processes and to save the data to disc in a variety of formats. In other terms, image processing is the process of neutering and analysing graphical information in photographs. In our lives, we frequently come across many types of image processing. The clearest example of image processing in our lives is our brain's perceiving of visuals. Once we perceive pictures with our eyes, the process takes relatively little time